Tracking the mid-infrared fine structure of quasi-1D excitons controlled by magnetic order - Liebich, M.; Florian, M.; Nilforoushan, N.; Mooshammer, F.; Mosina, K.; Sofer, Z.; Dirnberger, F.; Kira, M.; Huber, R.; Mooshammer, Fabian (International Conference on Infrared, Millimeter, and Terahertz Waves, IRMMW-THz, 2024)
We use phase-locked few-cycle mid-infrared pulses to probe internal Rydberg-like transitions of quasi-one-dimensional excitons in the magnetic semiconductor CrSBr. The experimentally observed fine structure encompasses a lifted degeneracy of the 2p states induced by the anisotropic optoelectronic properties of the crystal. Furthermore, the Coulomb correlations are effectively controlled via the magnetic structure. By inducing a phase transition from antiferromagnetic to paramagnetic states either thermally or by applying an external magnetic field, we can switch excitons from strongly bound and mono-layer-localized to weakly bound and interlayer-delocalized species. A state-of-the-art many-body theory fully captures these findings and identifies the spin restrictions of the interlayer tunneling. In the paramagnetic phase, the reduced quantum confinement lowers the binding energy and increases the phase space for scattering. This in situ control of Coulomb correlations opens a path to shape phase transitions on demand.
CRIS-Team Scopus Importer:2024-11-01
Keywords: anisotropic excitons; fine structure; mid-infrared spectroscopy; ultrafast dynamics; van der Waals magnets